Perencanaan kawasan karst sebagai kawasan geowisata di Kabupaten Grobogan, Jawa Tengah - Rahma, Reisya; Yusiana, Lury Sevita; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2020)
The Karst Area Planning as an Area Geotourism in Grobogan Regency of Central Java. The karst area in Grobogan Regency is a geological protected area that includes the Sukolilo Karst Landscape Area. The karst area has a lot of potential that can be used as a tourist attraction. The karst area requires a plan in suitable with the potential and constraints. The planning can be done by developing the karst area as a geotourism. This research method uses survey methods which stages are inventary, analysis, synthesis, concepts, and planning. In the assessment analysis of the 12 attractions there are 4 (four) that have high potential to be developed i.e. Lawa and Macan Caves, Gulingan Waterfall, Lamping Hill and Widuri Waterfall. The basic concept of this planning uses the concept of geotourism as a special interest tour developed into a spatial plan, activity plan and facility plan. The final result of this planning are the site plan of attraction Lawa and Macan Caves, Waterfall Gulingan, Lamping Hill and Widuri Waterfall as a Geotourism that is implemented in the karst of Grobogan Regency.